CONCEPT OF ADVANCED FLEXIBLE USE OF AIRSPACE - Luppo, Oleksandr; Argunov, Gennadiy; Mohyla, Andrii (Proceedings of National Aviation University (archive), 2016)
Purpose: Concept of Flexible Use of Airspace (FUA) allows to eliminate many problems on the basis of civil-military coordination, but there are still a lot of areas for improvement. These improvements will be implemented in the Advanced Flexible Use of Airspace (AFUA) concept. Methods: We examine the airspace structure in the frames of AFUA concept, which includes variable profile areas, temporary reserved and temporary segregated areas, danger or restricted areas. Mission Trajectory in AFUA which allows designing ad-hoc structures delineation at short notice is also examined. Regarding the performance enhancements of AFUA we compare these with FUA concept. Examination of AFUA structure gives us better view of the functions and opportunities of this concept. Result: AFUA concept provides many advantages for the civil aviation stakeholders and includes many other positive sides. Variable Profile Areas provide more flexibility, particularly in a high density traffic area and any combination of basic volume possible. Collaborative decision-making will increase the situational awareness of both parties and help to decrease the transit between airbases and training areas, allows military to use larger airspaces for missions on an absolute time-limited basis. As a result of mission trajectory implementation in AFUA concept general air traffic crossing are possible in all type of airspace structures, after coordination or under specific permanent agreements. The use of Centralized AFUA Services will allow the central collection, integration and provision of ASM data in support of continuous collaborative network processes, in such a way improving operational performance during the planning and execution phases (predictability, flexibility, better use of capacity, enhanced flight efficiency, real time sharing of information, better management of available airspace). Discussion: Given the important contribution that AFUA brings into air traffic management system, its main architectural components and performance enhancements, collaborative decision making process and concept’s implementation phases.